Biodegradable graphene oxide and polyaptamer DNA hybrid hydrogels for implantable drug delivery. (August 2016) - Kim, Mi-Gyeong; Shon, Yuna; Miao, Wenjun; Lee, Jaiwoo; Oh, Yu-Kyoung
Abstract: Here, we report an injectable and biodegradable hydrogel based on drug-specific DNA polyaptamer networks using graphene oxide nanosheets as a physical crosslinker. Polyaptamer DNA and graphene oxide (PA-GO) hybrid hydrogels were constructed by single-step rolling-circle amplification (RCA) of a DNA template in the presence of GO nanosheets. The DNA template for RCA was designed to contain a kanamycin (Kan)-aptamer sequence for specific and efficient drug loading and a GO-binding 12-mer oligo A sequence. PA-GO hybrid hydrogels exhibited a bird's nest-like surface morphology, a swelling ratio of 657% at 2 h, and viscoelasticity suitable for injection and retention. PA-GO hydrogel was degraded by deoxyribonuclease I. PA-GO hybrid hydrogels specifically bound Kan, exhibiting a drug loading efficiency of 58.0% for Kan compared with 1.5% for gentamicin. Kan-loaded PA-GO (Kan/PA-GO) hybrid hydrogels exerted antibacterial activity against gram-negative ( Escherichia coli ) and gram-positive ( Staphylococcus aureus ) bacteria. In mice, subcutaneously injected, fluorescent Kan-loaded PA-GO hybrid hydrogel was retained at the injection site and degraded with time. Our findings suggest the potential of PA-GO hybrid hydrogels constructed by single-step RCA for biomedical applications.